-(9-3x)-(4+2x)-4=-(2-5x)=-x

Simple and best practice solution for -(9-3x)-(4+2x)-4=-(2-5x)=-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(9-3x)-(4+2x)-4=-(2-5x)=-x equation:



-(9-3x)-(4+2x)-4=-(2-5x)=-x
We move all terms to the left:
-(9-3x)-(4+2x)-4-(-(2-5x))=0
We add all the numbers together, and all the variables
-(-3x+9)-(2x+4)-(-(-5x+2))-4=0
We get rid of parentheses
3x-2x-(-(-5x+2))-9-4-4=0
We calculate terms in parentheses: -(-(-5x+2)), so:
-(-5x+2)
We get rid of parentheses
5x-2
Back to the equation:
-(5x-2)
We add all the numbers together, and all the variables
x-(5x-2)-17=0
We get rid of parentheses
x-5x+2-17=0
We add all the numbers together, and all the variables
-4x-15=0
We move all terms containing x to the left, all other terms to the right
-4x=15
x=15/-4
x=-3+3/4

See similar equations:

| -4(1+7n)=-4+3n | | x/5-3=24 | | 10r^2+36=-66r | | 6a+5a=-13 | | 3/x-1/6x-26=13 | | 10/x-2+3=5x/x-2 | | -5u+3(u-2)=-14 | | (-7x-2x=3)-(9x-5x+4) | | 7(4a-4)=7-7a | | 15-12y=16 | | -22-8x=-5(3x-4) | | 10x-6=58-6x | | 15x-12)=16 | | 15(0)-12y=16 | | -5+4(5x+3)=367 | | (3+5)2x2-13=x | | (5x-12)+(2x+4)+90=180 | | 7x/11-19/14=11/2-5x/8 | | -2/3+3=1/3(-6x+21) | | x^2+5=5/1/16 | | -3r-3r=-18 | | (2x+1/3)+(5x+2/3)=(12x-4) | | 7v/11-19/14=11/2-5v/8 | | 5n+17=-3(1-5n) | | 3x-18=5x5 | | 3=-3p+2p | | x-0.1x=315000 | | 7/9b=49 | | x^2+5=51/16 | | 0.83*x=40 | | (.4)x=3500 | | y-1=5(+2) |

Equations solver categories